1982
DOI: 10.1136/bmj.284.6328.1519
|View full text |Cite
|
Sign up to set email alerts
|

Normality and reliability in the clinical assessment of backache.

Abstract: Backache is common yet its routine medical assessment is imprecise, unreliable, and poorly interpreted. Reproducibility studies on 475 patients improved the reliability of clinical interview and examination in backache, while studies of 335 normal subjects defined the limits of normality. Assessment of nerve function was found to be reliable but assessment of the back itself had to be considerably modified and examination improved by incorporating actual measurements. The validity and clinical utility of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
4

Year Published

1983
1983
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(37 citation statements)
references
References 8 publications
1
31
1
4
Order By: Relevance
“…Like other authors, the panel also noted the ongoing controversy regarding the existence of fibrositis, or its distinctness from myofascial pain syndromes. Though muscle spasm is frequently diagnosed, specialists working in the same clinic cannot agree when it is present (73). Controversy persists about the appropriate use and sequencing of expensive diagnostic procedures, such as computed tomography, magnetic resonance imaging, and myelography (injection of contrast material around the spinal cord) (39,77).…”
Section: Variability In Care: a Lack Of Therapeutic Consensusmentioning
confidence: 99%
“…Like other authors, the panel also noted the ongoing controversy regarding the existence of fibrositis, or its distinctness from myofascial pain syndromes. Though muscle spasm is frequently diagnosed, specialists working in the same clinic cannot agree when it is present (73). Controversy persists about the appropriate use and sequencing of expensive diagnostic procedures, such as computed tomography, magnetic resonance imaging, and myelography (injection of contrast material around the spinal cord) (39,77).…”
Section: Variability In Care: a Lack Of Therapeutic Consensusmentioning
confidence: 99%
“…Walsh et al (1990) found that pain behavior was also highly significant in the responders, disregarding the fact that Waddell in several articles during the eighties has demonstrated that a high level of pain or illness behavior precludes a satisfactory result from low back pain surgery (Waddell et al 1980, Waddell et al 1982, Waddell 1992.…”
mentioning
confidence: 99%
“…However, the terminology describing this postural/spinal displacement in the literature is indistinct and confusing. For example, descriptions such as ''lumbosacral list'' [1], ''trunk list'' [33,48,44,59], ''sciatic spinal deformity'' [37], ''alternating lumbar scoliosis'' [6,49], ''windswept spine'' [20], and ''side-gliding'' [16] have all been utilized for the description of lateral thoracic-cage translation.…”
Section: Introductionmentioning
confidence: 99%
“…Within the literature, reports of lateral thoracic translations in patients with acute lumbar disc herniation are also common [16,37,48,59]. However, this postural displacement can occur in LBP patients without disc herniation and in individuals without LBP [1,33].…”
Section: Introductionmentioning
confidence: 99%